Kajian Kebutuhan Prasarana dan Sarana Pendidikan Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang - Irwan Irwan; Andri Yulianto; Doharman Lumban Tungkup; Surnata Surnata; Fadjrin Wira Perdana (Departement of Mathematics Education, 2022)
This official school was first established with the FTA 170 Project agreement between the Government of the Kingdom of Belgium and the Government of the Republic of Indonesia on December 19, 1979. In an effort to meet the qualification needs in the field of river and lake transportation traffic, the River and Lake Transportation Training Center was formed (BPL LLASD) based on MENPAN Decree No. 537/5/MENPAN/10/87 dated October 5, 1987 and MENHUB Decree No. 231/HK.602/Phb-87 dated October 21, 1987 which only held short courses for students. In 1990, he received the Diploma III program in River, Lake, and Ferry Transport Traffic (LLASDP). Education and training as well as counseling are held through various training and counseling programs according to needs so that the programs implemented can run efficiently, optimally and effectively. One thing that is very important to realize the development of human resources is through the maximum participation of educational institutions, especially in the field of transportation. With the determination of the organizational structure, of course, we refer to the Regulation of the Minister of Education and Culture of the Republic of Indonesia No. 3 of 2020 concerning National Higher Education Standards. The progress of Polytechnics has increased from year to year so that we have recruited cadets from one study program to 3 study programs, namely the D-III MTPD Study Program, the D-III Ship Engineering Study Program and the D-III Nautical Study Program. From the results of this increase, there is still a lack of infrastructure in the placement of cadets, especially in terms of class facilities with an imbalance between students and cadet facilities.